Causal effects of genetically predicted type 2 diabetes mellitus on blood lipid profiles and concentration of particle-size-determined lipoprotein subclasses: A two-sample Mendelian randomization study - Chen, Ken; Zheng, Jilin; Shao, Chunli; Zhou, Qing; Yang, Jie; Huang, Tao; Tang, Yi-Da (Frontiers in Cardiovascular Medicine, 2022)
Background: Observational studies have shown inconsistent results of the associations between type 2 diabetes mellitus (T2DM) and blood lipid profiles, while there is also a lack of evidence from randomized controlled trials (RCTs) for the causal effects of T2DM on blood lipid profiles and lipoprotein subclasses. Objectives: Our study aimed at investigating the causal effects of T2DM on blood lipid profiles and concentration of particle-size-determined lipoprotein subclasses by using two-sample Mendelian Randomization (MR) method. Methods: We obtained genetic variants for T2DM and blood lipid profiles including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and total cholesterol (TC) from international genome-wide association studies (GWAS). Two-sample MR method was applied to explore the potential causal effects of genetically predicted T2DM on blood lipid profiles based on different databases respectively, and results from each MR analysis were further meta-analyzed to obtain the summary results. The causal effects of genetically predicted T2DM on concentration of different subclass of lipoproteins that determined by particle size were also involved in MR analysis. Results: Genetically predicted 1-unit higher log odds of T2DM had significant causal effect on higher level of TG (estimated β coefficient: 0.03, 95% confidence interval [CI]: 0.00 to 0.06) and lower level of HDL-C (estimated β coefficient: -0.09, 95% CI: -0.11 to -0.06). The causality of T2DM on the level of TC or LDL-C were not found (estimated β coefficient: -0.01, 95% CI: -0.02 to 0.01 for TC and estimated β coefficient: 0.01, 95% CI: -0.01 to 0.02 for LDL-C). For different size of lipoprotein particles, 1-unit higher log odds of T2DM was causally associated with higher level of small LDL particles, and lower level of medium HDL particles, large HDL particles and very large HDL particles. Conclusions: Evidence from our present study showed causal effects of T2DM on the level of TG, HDL-C, and concentration of different particle size of lipoprotein subclasses comprehensively, which might be particular helpful in illustrating the dyslipidemia experienced by patients with T2DM, and further indicating new treatment targets for these patients to prevent subsequent excessive cardiovascular events from a genetic point of view.